2001
DOI: 10.1037/0012-1649.37.6.826
|View full text |Cite
|
Sign up to set email alerts
|

Peekaboo: A new look at infants' perception of emotion expressions.

Abstract: Infants' responsiveness to others' affective expressions was investigated in the context of a peekaboo game. Forty 4-month-olds participated in a peekaboo game in which the typical happy/surprised expression was systematically replaced with a different emotion, depending on group assignment. Infants viewed three typical peekaboo trials followed by a change (anger, fear, or sadness) or no-change (happiness/surprise) trial, repeated over two blocks. Infants' looking time and affective responsiveness were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(108 citation statements)
references
References 56 publications
(122 reference statements)
5
99
0
4
Order By: Relevance
“…in infant-directed speech. A training tape was provided by Montague and Walker-Andrews (1999), which has been used as a training tape and stimuli in previous experiments (Kahana-Kalman & WalkerAndrews, 2001;Montague & Walker-Andrews, 2001. The tape consists of an actress who is familiar with the Facial Action Coding System (Ekman & Friesen, 1978) and has previous experience in presenting dynamic facial expressions displaying happy, sad, and angry audiovisual affective expressions.…”
Section: Experiments 1: the Development Of Sensitivity To Affect In Bimentioning
confidence: 99%
“…in infant-directed speech. A training tape was provided by Montague and Walker-Andrews (1999), which has been used as a training tape and stimuli in previous experiments (Kahana-Kalman & WalkerAndrews, 2001;Montague & Walker-Andrews, 2001. The tape consists of an actress who is familiar with the Facial Action Coding System (Ekman & Friesen, 1978) and has previous experience in presenting dynamic facial expressions displaying happy, sad, and angry audiovisual affective expressions.…”
Section: Experiments 1: the Development Of Sensitivity To Affect In Bimentioning
confidence: 99%
“…There is also evidence to suggest that infants are sensitive to facial expressions from a very early age (Montague and Walker-Andrews 2001), as they are to biological motion (eg Arterberry and Bornstein 2001). However, what is unknown is whether or not infants are sensitive to the motion component of these facial expressions.…”
mentioning
confidence: 99%
“…My colleagues and I have conducted several experiments targeting such effects. In one study (Montague & Walker-Andrews, 2001), infants were shown facial and vocal expressions (happy, sad, fearful, and angry) in the context of a game of peek-a-boo. Peek-aboo provides infants with a rich, natural context in which there is substantial spatial-temporal structure.…”
Section: The Perception Of Emotionmentioning
confidence: 99%